EXCLUSIVE BREASTFEEDING PRACTICE AND ASSOCIATED FACTORS AMONG FIRST-TIME MOTHER IN LARKANA - JAMEEL , A; SHAIKH, S; JAMEEL, S (Biological and Clinical Sciences Research Journal, 2024)
Exclusive breastfeeding (EBF) is defined as the practice of feedi: Exclusive breastfeeding (EBF) is defined as the practice of feeding infants solely with breast milk for the first six months of life, without introducing any other liquids or solid foods, except oral rehydration solutions, vitamins, or necessary medications. Objective: The main objective of the study is to find the exclusive breastfeeding practice and associated factors among first-time mothers in Larkana, Pakistan. Methods: This cross-sectional study was conducted at Sheikh Zayed Women's Hospital Larkana from June 2023 to December 2023. Data involve 345 breastfeeding first-time mothers as participants. Data were collected through a random sampling technique. Participants were first-time mothers with infants aged between 0-6 months, willing to provide informed consent were included in the study. Mothers with serious health conditions or those whose infants had medical complications preventing breastfeeding were excluded. Results: Data include 345 participants according to the criteria of the study. The majority of participants in the study were aged between 20-30 years (60.3%), with a smaller proportion under 20 years (9.3%) and over 30 years (30.4%). Most had secondary education or less (68%), while 32% had higher education. Regarding employment status, 59.4% were unemployed, and 40.6% were employed. In terms of socioeconomic status, 40% of participants were from low-income groups, 35% from middle-income, and 25% from high-income. In the study, 58% of participants reported practicing exclusive breastfeeding (EBF), while 42% did not. Conclusion: Exclusive breastfeeding rates among first-time mothers remain suboptimal, with significant factors such as maternal age, education, employment status, mode of delivery, and healthcare support playing key roles in influencing EBF practices.ng infants solely with breast milk for the first six months of life, without introducing any other liquids or solid foods, except oral rehydration solutions, vitamins, or necessary medications. Objective: The main objective of the study is to find the exclusive breast-feeding practice and associated factors among first-time mothers in Larkana, Pakistan. Methodology: This cross-sectional study was conducted at Sheikh Zayed Women Hospital Larkana during June 2023 till December 2023. Data involve 345 breast feeding first-time mothers as participants. Data were collected through a random sampling technique. Participants were first-time mothers with infants aged between 0-6 months, willing to provide informed consent were included in the study. Mothers with serious health conditions or those whose infants had medical complications preventing breastfeeding were excluded. Results: Data include 345 participants according to the criteria of the study. The majority of participants in the study were aged between 20-30 years (60.3%), with a smaller proportion under 20 years (9.3%) and over 30 years (30.4%). Most had secondary education or less (68%), while 32% had higher education. Regarding employment status, 59.4% were unemployed, and 40.6% were employed. In terms of socioeconomic status, 40% of participants were from low-income groups, 35% from middle-income, and 25% from high-income. In the study, 58% of participants reported practicing exclusive breastfeeding (EBF), while 42% did not. Conclusion: Exclusive breastfeeding rates among first-time mothers remain suboptimal, with significant factors such as maternal age, education, employment status, mode of delivery, and healthcare support playing key roles in influencing EBF practices.